Variability of antioxidant compounds and capacities in four wild fruits collected in different years and locations in Mozambique - Eulália Uaila; Yvonne Granfeldt; Maida Khan; Isabel Guiamba; Stephen Burleigh; Claudia E. Lazarte (Journal of Agriculture and Food Research)
This study investigated the variability of antioxidant compounds and capacity of four wild edible fruits from Mozambique: Adansonia digitata (AD), Dialium schlechteri (DS), Garcinia livingstonei (GL), and Syzygium cordatum (SC), collected over three consecutive years from seven locations. Antioxidant compounds including total polyphenol content (TPC), total flavonoid content (TFC), and vitamin C, as well as the total antioxidant capacity (TAC) by three methods (DPPH, ABTS, and FRAP) were determined by spectrophotometric methods. Results in dry basis for TPC ranged from 42.8 ± 1.05 to 65.4 ± 0.51 mg GAE/g, TFC from 8.6 ± 0.03 to 66.7 ± 1.41 mg RE/g and, vitamin C from 1.7 ± 0.28 to 40.1 ± 0.35 mg/100 g. TAC-DPPH ranged from 53.5 ± 1.80 to 88.3 ± 0.29 μmol TE/g, TAC-ABTS from 52.8 ± 0.50 to 136.7 ± 0.97, μmol TE/g, and TAC-FRAP from 12.4 ± 0.79 to 75.0 ± 2.32 μmol TE/g. AD exhibited the highest TPC and vitamin C, indicating higher antioxidant capacity. Notably, yearly variations had a more pronounced impact on antioxidant compounds than locations. It was found a yearly variation of about 30 % for TFC in SC and vitamin C in AD. Despite these variations, these underutilized fruits hold potential nutritional and health benefits and can be used in food product development.